Telang Flower Extract (Clitoria Ternatea) as Antioxidant in Snack Sticks - Fangohoi, Latarus; Aimanah, Ummu; Munira, Munira; L, Andi Besse Sumpala (Jurnal Penelitian Pertanian Terapan, 2023)
Telang flower (Clitoria ternatea) is a flower that can be grown as an ornamental plant or as a wild plant. It has long been used in traditional medicine and as a food coloring because it contains a number of active ingredients with pharmacological potential. Snack sticks can improve organoleptic quality and antioxidant activity content, this study aims to determine the organoleptic quality, and antioxidant activity content and to find out how to make snack sticks against the addition of telang flower extract as an antioxidant on snack sticks. The study method used was an experimental method of Completely Randomized Design (CRD).The sudy method used was the completely randomized design (CRD) experimental method, organoleptic tests and antioxidant tests using the DPPH method and the Duncan method with 5 treatments and 3 replications resulting in 15 experimental units with each experiment, namely P0 = no treatment, P1 = 10g telang flower extract + 100ml water, P2 = 20g extract telang flower + 100ml water, P3 = 30g telang flower extract + 100ml water, P4 = 40g telang flower extract + 100ml water. The results showed that the P4 treatment (40g telang flower extract + 100ml water) gave the best results on organoleptic quality with an average score of 11.6, and the best content of antioxidant activity was found in P4 treatment with an amount of 103.52 ppm.